THE RELATIONSHIP BETWEEN LEARNING INTEREST AND LEARNING ENVIRONMENT AT HOME WITH MATHEMATICS LEARNING OUTCOMES - Ardati Swastia Saputro; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Mathematics learning result is related to many factors. Learning interest and learning environment at home are some factors that are suspected to be related to the student's mathematics learning result. The study aims to determine whether there is a positive and significant correlation between learning interest and learning environment at home with mathematics learning results of student grade VIII at State Junior High School (SMP N) 1 Sedayu Bantul, even semester academic year 2018/2019. The study population was students of grades VIII B, VIII C, VIII D, VIII E, VIII F, and VIII G of SMP N 1 Sedayu Bantul, even semester academic year 2018/2019 with a total of 188 students. A random sampling technique took the sample to class, and it was obtained that class VIII E consisted of 31 students. The data collection technique was used questionnaires and tests. The research instrument test was used as a validity test, a reliability test, and a different power test. The prerequisite tests analysis included a normality test, an independent test, and a linearity test. The analysis of data was used correlation analysis and linear regression analysis. The research result indicates that there is a positive and significant correlation between learning interest ( ) and the learning environment at home ( ) with mathematics learning result with  or  with , and .                                                                 , and , , , and   ..